Finanse samorządu terytorialnego Cesarstwa Japonii - Babczuk, Arkadiusz (Finance of Self-Governments in Japan, 2005)
The finance of local and regional self- governments in Japan is the object of the present study. The author characterizes the principles of their organization and their role in the public sector. He presents basic sources of revenue of prefectures (regional self-governments) as well as local self- governments, and also the main directions of their expenditures. The debt of the self-governmental sector is presented then. Finally, the author characterizes the changes in finance of self-governments which are already made to self-governmental sector in Japan so that it would function in an efficient way.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 50-63